Travel Pattern and Pandemic; How Do Travel Preferences Effects The Changes In Expenses In New Normal Era? - Ni Ketut Wiwiek Agustina; Della Sharyputra (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2022)
The Covid-19 pandemic caused various new lifestyle changes, one of which was travel activities. Changes in patterns and habits make tourists' interest in accommodation, tourist attractions, transportation, to cleanliness a lot of considerations. This research aims to review the factors a tourist considers in travelling, the budget during the trip, and travel references with research loci in Bali. In this study, the data used quantitative data from questionnaire results which were then processed using SPSS. The research team used a non-probability sampling method with purposive sampling techniques to determine respondents. This study showed that some respondents were more concerned with health aspects when travelling, which affected tourists' expenses during travel to Bali due to changes in tourist preferences.